Relationship of low birth weight and socioeconomic factors: a case-control study in tertiary care centre in north Kerala - Pandarekandy, Seena T.; Chandran, Jyoti R.; Maliekkal, Jean; Balakrishnan, Ajitha; Edakkoth, Sreekumaran; Varancheri, Jowhara P. (International Journal Of Community Medicine And Public Health, 2025)
Background: Low birth weight (LBW) is an important indicator of infant mortality in our community. Though the studies were conducted on LBW with various risk factors all over the world, no studies were on Kuppuswamy socioeconomic status and relationships of LBW. Hence, this study was aimed to evaluate the socioeconomic factors associated with LBW using the modified Kuppuswamy SES 2022 version. Methods: A case-control study was designed using consecutive sampling as per patient registration in the first four months of the year 2023. A total of 452 newborn babies were taken. Of these, 171 cases and 217 control groups were taken. An independent student’s t-test was used for the comparison of the mean values of the study groups. The comparison of frequency across categories was done using the chi-square test. Maternal risk and new born outcome were calculated using odds ratio. Results: The study revealed that there was a significant difference between the mean Kuppuswamy SES scores among the study group. The scores were 10±3.8 and 11±4.3 for the case and control groups, respectively. This suggests that the case group is represented in socioeconomic class IV and was in poorer categories than the control group. Conclusions: The present study revealed that there was a significant correlation between modified Kuppuswamy SES 2022 version and low birth weight. Another finding from the study was that mothers with a low body mass index (BMI) during the pregnancy period are more likely to have low birth weight babies than mothers with a normal BMI.